THE QUALITY IMPROVEMENT IN ICT APPLICATION FOR INDONESIAN LANGUAGE LEARNING THROUGH LESSON STUDY FOR LEARNING COMMUNITY - Restu Bias Primandhika; Dida Firmansyah (Kopertis Region IV Jabar and Banten, 2018)
This article discusses the practice of lesson study conducted in the higher level of education in order to design a better lesson in ICT Application for Indonesian Language Learning. This study has done in one class of Indonesian Language Study Programme involving two role-model teachers with three observers as a team. The team was involved in designing, observing and evaluating each lesson that is conducted in two cycles. The lesson materials are the use of Microsoft Office for editorial purpose as the study programme specialty, such as 1) the basic skills of proof-reading tools in Word 2) write a mind-mapping style notes and journalist organization in OneNote 3) typography, writing style and adaptation for article publishing. The result shows that the practice of lesson study improves the learning quality both for teachers and student activities, especially in collaboration, communication, critical thinking ability and also creativity.